Anti Forensik Voice Note Menggunakan Whatsapp Mod - Mardlatillah, Hanifah; Prayudi, Yudi; Ramadhani, Erika (Universitas Negeri Gorontalo, 2023)
Currently there is a social media application that provides additional features in the form of voice changers by utilizing the voice note feature of Whatsapp Mod which can blur the identity of the voice owner. In several articles, Whatsapp Mod claims that this application is an anti-banned application, so it is feared that Whatsapp Mod is an application that uses anti-forensic techniques in it. This study aims to prove whether voice modifiers using voice notes on Whatsapp Mod can be a form of anti-forensic activity which can later make it difficult for investigators to conduct investigations. This will be proven by the use of a special method in handling audio forensics in which there are four stages, namely Acquisition, Enhancement, Decoding, and Voice Recognition. Audio forensics analysis that was carried out between voice recordings modified using Whatsapp Mod voice notes and original voice recordings showed results that were not identical. This proves that the voice modifier using the Whatsapp Mod voice note is considered an effective anti-forensic tool.